POPULASI LARVA Plutella xylostella Linn. PADA TANAMAN KUBIS DI KELURAHAN PASLATEN KECAMATAN TOMOHON TIMUR KOTA TOMOHON - Wailan M. Pandeirot; Noni N. Wanta; Betsy A.N. Pinaria (Universitas Sam Ratulangi, 2015)
ABSTRACT This study aims to determine the pest populations of P. xylostella in cabbage plants in the Paslaten village East Tomohon Tomohon sub district. This research was carried out by making a demonstration plot with three sub-plots. The results showed that the population of P. xylostella larval instars three and four on cabbage in the Village Paslaten East Tomohon Tomohon sub district in the rainy season ranged from 0 to 0.73 individual crop. P. xylostella larvae population is low from the first to the last observation. The low pest populations of P. xylostella at the time of the research is influenced by three factors: the first factor of climate especially rainfall with high intensity, the second factor D. eucerophaga parasitism natural enemies, and the third is a competition looking for food with other species of pests. Keywords: population, P. xylostella, Cabbage